Lithium CPS based on carboxylic fabric with CNT synthesized on its fibers' surface. (2017) - Zaurbekova, Z.; Chikhray, Y.; Ponkratov, Y.; Baklanov, V.; Abdullin, K.; Kulsartov, T.; Gordienko, Y.; Tazhibayeva, I.; Skakov, M.; Mukanova, A.
Abstract: The paper describes a technique of CNT synthesis on the fibers of carboxylic fabric. It consists of three operational stages: creation of the experimental facility based on high-temperature quartz flow reactor; validation of synthesis modes of CNT homogeneous layers, and CNT synthesis on the fibers of carboxylic fabric. An overview of the technology of lithium CPS production based on CNT-reinforced carboxylic fabric is given. It includes a development of experimental device for lithium CPS production, development and definition of technological procedures for CPS matrix filling with liquid lithium and manufacturing of prototype lithium CPS sample on basis of CNT-reinforced carboxylic fabric.